Green's Function for A Piecewise Continous Potential via Integral Equations Method - Brahim, Benali; Meftah, Mohammed Tayeb; Vandana, Rai (IndoMS, 2018)
The aim of this work is to provide Green's function for the Schrodingerequation. The potential part in the Hamiltonian is piecewise continuous operator.It is a zero operator on a disk of radius